KEPATUHAN HUKUM IBU TERHADAP KETENTUAN PIDANA TERKAIT PERBUATAN YANG MENGAKIBATKAN PENDERITAAN PSIKIS ANAK - Windayani, Tisa (Veritas et Justitia, 2018)
Art 80 and Art 76C  of Law No. 35/2014 purports to protect children from domestic violence (including most importantly those committed by the mother of the child).  This article using empirical juridical purports to analyze what factors are influential in determining compliance.  Primary data is collected using purposive sampling technique and subsequently is analyzed qualitatively.  The main result of the research is that avoidance of penal sanction is not a significant role in determining legal compliance.  More significant or influential are factors such as the extent or level of understanding the rule’s purpose or values behind the existing rule (prohibiting domestic violence), the need to maintain good relationship with the child; identification of the mother with certain groups in society and personal values.